Kurven auf Hyperflächen im Raum mit verallgemeinertem euklidischen Zusammenhang - Bliznikas, V. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Близникас. Кривые на гиперповерхности пространства обобщенной евклидовой связности V. Bliznikas. Apibendrinto Euklidinio sąryšio erdvės hiperpaviršinės kreivės